Calculating The Phosphor Concentration in Water of Tigris by (DNAA) Technique - B.J Hussein; D.A.AL-Munneem (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2005)
Samples of water from some cities on Tigris river have been used to determine the concentration by the derivative activation analysis (DNAA) technique. Phosphor concentration was neutron determined by preparing complex (Phosphor Vanadium Moly date) ion P:V ratio of 1:2 After extraction by reagent organic MIBK and irradiation. The concentration was found to be (1.503-2.607) ppm.